The dynamin-related protein PfDyn2 is essential for both apicoplast and mitochondrial fission in Plasmodium falciparum - Alexander A. Morano; Wei Xu; Francesca M. Navarro; Neeta Shadija; Jeffrey D. Dvorin; Hangjun Ke (mBio)
ABSTRACT Dynamins, or dynamin-related proteins (DRPs), are large mechano-sensitive GTPases that mediate membrane dynamics or organellar fission/fusion events. Plasmodium falciparum encodes three dynamin-like proteins whose functions are poorly understood. Here, we demonstrate that one of these dynamin-related proteins, PfDyn2, is required to divide both the apicoplast and the mitochondrion, a striking divergence from the biology of related parasites. Using super-resolution and ultrastructure expansion microscopy (U-ExM), we show that PfDyn2 is expressed in dividing schizonts, and that it localizes to both the apicoplast and the mitochondrion. Our use of long-term, live-cell microscopy allows for the visualization of apicoplast and mitochondrial division in live parasites at super resolution for the first time, and demonstrates that in PfDyn2-deficient parasites, while the apicoplast and mitochondrion increase in size and complexity, they do not undergo fission. We also show that these organellar fission defects prevent successful individualization of the schizont mass and the formation of new daughter cells, or merozoites because the basal complex, the cytokinetic ring of Plasmodium, cannot fully contract in PfDyn2-deficient parasites, a phenotype secondary to physical blockage by undivided organelles occluding the ring. PfDyn2’s singular role in mediating both apicoplast and mitochondrial fission has not been observed in other organisms possessing two endosymbiotic organelles, including other Apicomplexans, thus reflecting a unique, potentially exploitable method of organellar division in P. falciparum.IMPORTANCEPlasmodium falciparum remains a significant global pathogen, causing over 200 million infections and over 600,000 deaths per year. One significant obstacle to the control of malaria is increasing resistance to first-line artemisinin-based antimalarials. Another is a lack of basic knowledge about the cell biology of the parasite. Along with the mitochondrion, Plasmodium contains a second organelle descended from an endosymbiotic event, the apicoplast. Both organelles are common targets for antimalarials, but because many proteins involved in organellar fission are not conserved in Plasmodium, until now, the mechanisms underlying apicoplast and mitochondrial division have been unknown. In this study, we demonstrate that PfDyn2, a dynamin-related protein (DRP), is required for the division of both organelles. We also show that defects in organellar division hinder segmentation of the schizont and formation of invasive merozoites by preventing full contraction of the basal complex. By demonstrating its necessity for the proper division of both the apicoplast and the mitochondria, this study highlights PfDyn2 as a potential target for new antimalarials.